Improving the Ability to Recognize Primary Color Using Plastisifor Children Tunagrahita Light Class III in SLB Luki Padang - Ajismanto Ajismanto; Yarmis Hasan (EDUCATIO : Journal of Education, 2019)
This research is motivated by the discovery of a problem of a mentally regard development that is a mild category of a nine-year-old boy whose initials AD is in class III at SLB Luki Padang. Where the child has problems in recognizing basic colors. The purpose of this study was to improve the ability to recognize basic colors using plasticine for mentally disabled children in mild class IIprimaryss at SLB Luki Padang. This type of research is single-subject research (SSR) with A-B design. Data collected through direct observation and recorded on the observation sheet. The data analyzed is using graphical visual analysis. The results showed that the ability to recognize primary colors in mentally disabled children in the mild category class III in SLB Luki Padang increased after being given an intervention using plasticine. At baseline conditions, children get the highest score of 10%, and in the intervention conditions, children get a score of 90%. Thus it is proven that using plasticine can improve the ability to recognize basic colors for mentally disabled children in the light class III class at SLB Luki Padang.